Income Distribution and Growth Models: A Sectoral Balances Approach. (September 2019) - Behringer, Jan; van Treeck, Till
This article revisits the macroeconomic foundations and political economy of national growth models. It argues that the neo-Kaleckian model, which inspired the emergent growth model perspective and focuses primarily on the functional income distribution, can be usefully complemented by theories of private household consumption that focus on the personal distribution of income. The examples of the export-led and debt-led growth models of Germany and the United States, respectively, show how institutional differences help to explain why different countries developed different patterns of income distribution and how income distribution and institutions interacted to generate financial imbalances in different sectors of the economy (i.e., the private household sector, the private corporate sector, and the government sector).